2021
DOI: 10.1039/d0me00167h
|View full text |Cite
|
Sign up to set email alerts
|

Designing bioinspired green nanosilicas using statistical and machine learning approaches

Abstract: This is a first comparison of the sequential design of experiments strategy and global sensitivity analysis for nanomaterials, thus enabling sustainable product and process design in future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“… Overview of BIS synthesis, formation pathways, their compositional subtypes, and particle structures. (a) The chemical formation of bioinspired silica (image reproduced with permission from Dewulf et al) 16 and (b) the physical formation of bioinspired silica. (c) Three compositional subtypes of bioinspired silica.…”
Section: Overview Of Bioinspired Silicamentioning
confidence: 99%
See 3 more Smart Citations
“… Overview of BIS synthesis, formation pathways, their compositional subtypes, and particle structures. (a) The chemical formation of bioinspired silica (image reproduced with permission from Dewulf et al) 16 and (b) the physical formation of bioinspired silica. (c) Three compositional subtypes of bioinspired silica.…”
Section: Overview Of Bioinspired Silicamentioning
confidence: 99%
“…The gray region enables to synthesize silica with the constraints that the yield should exceed 60 mol % and the BET surface area should exceed 100 m 2 /g. Figures reproduced with permission from Dewulf et al 16 …”
Section: Production Capabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that Si precursor concentration and Si:N ratio determine the precipitation occurrence. An optimization regarding the reduction of the effort spent in experimental verification was realized by using a sequential design in order to efficiently perform pre-screening and screening, and subsequently the optimization of the experiments [ 69 ].…”
Section: In Silico Materials Developmentmentioning
confidence: 99%